Cell-Free Fermentation Broth of Bacillus velezensis Strain S3-1 Improves Pak Choi Nutritional Quality and Changes the Bacterial Community Structure of the Rhizosphere Soil - Lu, Kaiheng; Jin, Qing; Lin, Yibo; Lu, Wenwei; Li, Songshuo; Zhou, Chenhao; Jin, Jieren; Jiang, Qiuyan; Ling, Lichen; Xiao, Ming (Frontiers in Microbiology, 2020)
Bacillus velezensis is a plant growth-promoting rhizobacteria (PGPR) that has long been proven to improve the growth of plants, and it has been widely used in agriculture. However, in many reports, we observed that during the application of bacterial fluids, it appeared that the effect of the cell-free fermentation broth (CFB) was ignored. The purpose of this study is to compare the effect of the no inoculation treatment (CK), the B. velezensis strain S3-1 treatment (S), the CFB treatment in the Pak choi, soil bacterial community structure, soil enzyme activity, and field soil properties. The results have shown that, compared to the inoculation B. velezensis strain S3-1 treatment and the no-inoculation treatment; the inoculation of the CFB treatment can significantly enhance the soluble protein, soluble solids, ascorbic acid of Pak choi and increase the total phosphorus content and electrical conductivity (EC) in the soil. Based on high-throughput sequencing data, our analysis of soil microbial communities used R, NETWORK, and PICRUSt showed that the CFB treatment can enhance the relative abundance of Acidobacteria in the soil, decrease the abundance of native Bacillus in the soil, change the microbial community structure of the top 50 operational taxonomic units (OTUs), and improve soil microbial carbon metabolism and nitrogen metabolism. Overall, we observed that CFB treatment can also improve plant nutrition and change soil microbial communities. This study provides new insights for the application of microbial fertilizers in agricultural production.